Fragility of marine photosynthesis - Kovač, Žarko; Sathyendranath, Shubha (Frontiers in Marine Science, 2022)
Ecosystem fragility is an often used term in oceanography yet to this day it lacks a precise and widely accepted definition. Defining and subsequently quantifying fragility would be of great value, for such measures could be used to objectively ascertain the level of risk marine ecosystems face. Risk assessments could further be used to define the level of protection a given ocean region requires from economic activity, such as fisheries. With this aim we introduce to the oceanographic literature the concepts of marginal production and fragility, which we define for marine photosynthesis, the base of the oceanic food web. We demonstrate that marine photosynthesis is always fragile with respect to light, implying variability in surface irradiance acts unfavourably on biomass. We also demonstrate that marine photosynthesis can be both fragile and antifragile with respect to the mixed-layer depth, implying variability in mixed-layer depth can act both favourably and unfavourably on biomass. Quantification of marginal production and fragility is presented on data from two open ocean stations: Hawaii Ocean Time Series and Bermuda Atlantic Time-Series Study. Seasonal cycle of biomass is modelled and the effects of primary production fragility are analysed. A new tipping point for marine phytoplankton is identified in the form of a depth horizon. Using the new definitions presented here a rich archive of data can be used straightforwardly to quantify primary production fragility. The definitions can also be used to predict when primary production enters the fragile state during the seasonal cycle.